Berberian sound studio [videorecording (DVD)] - Jones, Toby, 1966-; Strickland, Peter, 1973- (Mpi Media Group., 2013)
When a British sound engineer takes on a job working with an Italian horror film director, the gruesome content of the movie causes his fragile psyche to unravel.